The Diagnostic and Prognostic Values of NCR1 and NCR3 Genes in Iraqi Breast Cancer Women - Najm, Mohammed A. (Iraqi Journal of Cancer and Medical Genetics, 2016)
Background: The Natural cytotoxicity receptors (NCR1 and NCR3) have been classically defined as activating receptors delivering potent signals to Natural Killer (NK) cells in order to lyse harmful cells and to produce inflammatory cytokines. Indeed, the elicitation of NK cells effector functions after engagement of NCRs with their ligands on tumor cells without the need for prior antigen recognition is one of the main mechanisms that allow a rapid clearance of tumor cells. Objectives: Evaluation of the diagnostic and/or prognostic values of NCR1 and NCR3 genes in breast cancer Iraqi females patients by initially comparing the expression concentrations of these genes between breast cancer patients and control group, then, comparing the expression levels of these genes with certain clinical features among breast cancer patients (ages of patients, tumor grade, tumor stage and the presence or absence of metastasis). Material and Methods: The NCR1 and NCR3 levels were determined in tissue samples (Formalin Fixed Paraffin Embedded Tissue “FFPE”) derived from 51 Invasive Ductal Carcinoma women and 33 benign breast tumor women (control group) were attended to the Medical City and Al-Yarmouk teaching laboratories / Baghdad – Iraq. The patients’ samples were subjected to total RNA extraction, and then to molecular study by using reverse transcription and quantitative real time PCR at Molecular Oncology Unit in Guy´s Hospital – Kings College / London – UK. Results: The expression of NCR1 and NCR3 genes were detected in 43 (84.31%) and 41 (80.39%) of breast cancer patients respectively, also, the levels of these genes showed high significant increase in breast cancer patients compared to control group. Furthermore, there were a gradual increase in the NCR1 and NCR3 expression concentrations with disease grades and stages progression (significant for both genes) in patients with primary breast cancer, moreover, the metastatic breast cancer patients showed significant decrease in NCR1 and NCR3 levels compared to primary breast cancer patients. There were no significant differences in the levels of NCR1 and NCR3 genes among the age groups of patients. Conclusions: The present study results reflect the potential utility of NCR1 and NCR3 as noninvasive markers for detecting breast cancer even in the earliest cancer stages, also, they suggest the possibility of using these genes as an efficient molecular signatures for detecting breast cancer disease progression, discrimination between different stages and grades of breast tumors, and its might be of value as a prognostic markers.